Outcomes of percutaneous intervention in in-stent versus de-novo chronic total occlusion: a meta-analysis. (1st November 2020) - Mir, Tanveer; Ullah, Waqas; Sattar, Yasar; Al-Khadra, Yasser; Darmoch, Fahed; Pacha, Homam Moussa; Alraies, M Chadi
ABSTRACT: Background: Chronic total occlusion (CTO) is defined as coronary artery obstruction with no luminal continuity. Comparative outcomes of PCI in patients with in-stent CTO (IS-CTO) versus de-novo CTO are unclear. Methods: An extensive literature search was done for outcomes of PCI in patients undergoing IS-CTO and de-novo CTO. The primary endpoint was major adverse cardiac events (MACE) and secondary endpoints were cardiovascular mortality, MI, and procedural success. Odds ratio (OR) with a 95% confidence interval (CI) was calculated using RevMan 5.3. Results: Five studies consisting of 3, 681 patients (IS-CTO = 464, de-novo CTO = 3, 217) were included. PCI in IS-CTO was associated with a significantly higher odds of MACE (OR 2.21, 95% CI 1.32–3.68, p = 0.002) and MI (OR 4.31, 95% CI 1.94–9.58, p = 0.0003) compared to patients with de-novo CTO. Mortality outcome (OR 1.49, 95% CI 0.93–2.39, p = 0.10) between the two groups was similar. Overall odds of procedural-success were similar among the groups (OR 1.11, 95% CI 0.84–1.46, p = 0.47). Conclusion: PCI for in-stent CTO might be associated with higher odds of MACE and MI compared to PCI for de-novo CTO. However, cardiovascular mortality or failure of procedure are similar.